Features of modeling fatty liver disease in rats of different ages based on a high-calorie diet - R. V. Yanko; E. G. Chaka; A. S. Zinchenko; S. L. Safonov; M. L. Levashov (Ожирение и метаболизм, 2022)
BACKGROUND: The problem of diagnosis, treatment and prevention of fat liver disease (FLD) is one of the actual problems of modern medicine. In this regard, the need for the creation of reliable experimental models of the FLD, which would be as close as possible to the pathogenetic patterns of the development of this disease in humans.AIM: To create an experimental model of FLD and compare the efficiency of its reproduction in rats of different ages.MATERIALS AND METHODS: The study was conducted on male Wistar rats, whose ages at the beginning of the experiment were 3 and 18 months. Control animals were fed a standard diet. The experimental rats were kept on a diet with excess fat (45 %) and carbohydrates (31 %) for 12 weeks. The liver tissue samples were taken for morphological studies of FLD. Histological preparations were made according to the standard technique. Morphometry on digital images of micropreparations was conducted using the computer program «IMAGE J». The concentration of lipids, cholesterol, and triglecerides in the liver tissue was determined, and the concentration of ALT in the blood serum was determined. To assess the biophysical properties of the liver tissue, the method of multifrequency bioimpedance measurement was used.RESULTS: The transfer of animals to a high-calorie diet developed by us led to the development of FLD. This was evidenced by an increase of the liver mass, its pale shade and soft consistency. Morphometric signs of FLD were also revealed. Hypertrophy of hepatocytes was observed with a simultaneous decrease in the nuclear-cytoplasmic ratio; accumulation of numerous lipid inclusions in the cytoplasm and the appearance of large lipid droplets replacing the voids of dead hepatocytes. The number of binuclear hepatocytes and nucleolus in the nucleus, the relative area of the sinusoid network were decreased. An increase in the concentration of lipids, cholesterol and triglecerides in the liver tissue of experimental rats, as well as the activity of ALT in the blood serum, was observed. Changes in the bioimpedance measurements of the liver tissue also indicated the  development of severe fatty degeneration of the liver in both young (to a greater extent) and old rats.CONCLUSION: The model of FLD we have advanced based on a combined (fat-carbohydrate) high-calorie diet. It leads to the development of pronounced morphological, biochemical and biophysical signs of this pathology in all experimental rats. The most pronounced manifestations of FLD are observed in young animals.